Carbon-Based Materials/Latex Composite from Euphorbia Tirucalli Plant for Potential Bone Fracture Treatment - Supardi; Wardani, Pranita; Dwandaru, Wipsar Sunu Brams Dwandaru (Malaysian Journal of Science, 2025)
This study aims to investigate the preparation and characterization of carbon-based materials (CMs)/latex composites from the Euphorbia tirucalli plant for potential bone fracture treatment. The primary objectives are to: i) determine the antibacterial property of the CMs/latex composites against Staphylococcus aureus bacteria; and ii) determine the tensile strength of the CMs/latex composites via chicken bones as the model. The CMs were prepared using a simple heating method, using an oven at a temperature of 250 oC. The CMs/latex composites were prepared by mixing 3 ml of the latex and CMs solutions with concentrations of 10%, 20%, and 40% in 10 ml of distilled water. The CMs were characterized using UV-Vis, PL, and FTIR spectroscopies. The antibacterial property and tensile strength of the CMs/latex composites were tested using the diffusion method and an ultimate testing machine, respectively. The results obtained demonstrate that the CMs had absorption and emission peaks at wavelengths of 287 nm and 499 nm, respectively, resulting in cyan luminescence. The FTIR test of the CMs indicated the existence of the C=C, O-H, and N=C=S functional groups. The CMs/latex composites produced the highest diameter of inhibition zone and tensile strength of 3.24 mm and 0.02 kN, respectively. These findings concern the potential application of CMs/latex composites for bone fracture treatment with antibacterial properties.